Novel processing of bioglass ceramics from silicone resins containing micro‐ and nano‐sized oxide particle fillers. Issue 8 (29th August 2013) - Fiocco, L.; Bernardo, E.; Colombo, P.; Cacciotti, I.; Bianco, A.; Bellucci, D.; Sola, A.; Cannillo, V.
Abstract Highly porous scaffolds with composition similar to those of 45S5 and 58S bioglasses were successfully produced by an innovative processing method based on preceramic polymers containing micro‐ and nano‐sized fillers. Silica from the decomposition of the silicone resins reacted with the oxides deriving from the fillers, yielding glass ceramic components after heating at 1000°C. Despite the limited mechanical strength, the obtained samples possessed suitable porous architecture and promising biocompatibility and bioactivity characteristics, as testified by preliminary in vitro tests. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2502–2510, 2014.